Effects of pain on the facial expressions of goat kids - A. Argüello; Marta González-Cabrera; Antonio Morales-delaNuez; Lorenzo Enrique Hernández-Castellano; Sergio Martín; Noemí Castro (Journal of Applied Animal Research)
Pain assessment is essential in laboratory and farm animals. Grimace scales have been used for this purpose since 2010. The aim of the present study was to investigate how pain (due to disease presence) affects the main facial expressions of goat kids. For this purpose, 60 goat kids aged 1 to 20 days were included in the study. An experienced veterinarian graded the animals’ pain based on his experience (pain 0, 1, and 2), and two photographs (frontal and lateral) were taken. The following measurements were recorded: Height and width of the palpebral fissure, mouth angle, angles of the nose in profile and front. Pain level affected the height (0.83 and 1.29 cm, pain level 0 and 2 respectively, p < 0.001) and width of the palpebral fissure (1.85 and 2.35 cm, pain level 0 and 2 respectively, p < 0.001), which increased at pain level 2. Thus, narrowing of the eye was not observed when pain level increased. The angle of the mouth increased at pain level 2 (39.2 and 41.0 degrees, pain level 0 and 2 respectively, p = 0.013), and the frontal angle of the nose decreased at pain level 2 (93.5 and 85.0 degrees, pain level 0 and 2 respectively, p = 0.009).